2023
DOI: 10.2147/ijnrd.s363133
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Management in the Middle East and Africa: Concerns, Challenges, and Novel Approaches

Abstract: The burden of chronic kidney disease (CKD) and other comorbidities, such as hypertension and diabetes, which increase the risk of developing CKD, is on the rise in the Middle East and Africa. The Middle East and Africa CKD (MEA-CKD) steering committee, comprising eminent healthcare specialists from the Middle East and Africa, was formed to identify and propose steps to address the gaps in the management of CKD in these regions. The current article lists the MEA-CKD steering committee meeting outcomes and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The occurrence of ESKD in the Middle East, covering countries like Iran, Egypt, Turkey, Tunisia, Yemen, Syria, Lebanon, Qatar, and Iraq, varied from 55 to 818 per million population. Additionally, the prevalence of CKD stages 3–5 in Abu Dhabi was reported as 2.8% in females and 4.6% in males 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of ESKD in the Middle East, covering countries like Iran, Egypt, Turkey, Tunisia, Yemen, Syria, Lebanon, Qatar, and Iraq, varied from 55 to 818 per million population. Additionally, the prevalence of CKD stages 3–5 in Abu Dhabi was reported as 2.8% in females and 4.6% in males 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The experts were defined as specialists in nephrology, endocrinology/diabetology, internal medicine and primary care medicine who had achieved an appropriate level of seniority within their field (eg, professors, clinical directors), or had published papers related to the management of CKD/HF/Diabetes, or had been involved in guidelines development. [13][14][15][16][17][18][19][20][21] The steering group members were selected to provide representation across a range of development indicator levels external to Europe and North America (to avoid replication of previous published work 22 ). Steering group members were recruited to represent countries outside of North America and Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Ghamdi et al, suggested that national renal associations, nephrology conferences, and memorial days such as World Kidney Day can be used to raise awareness at patients and PCPs levels about novel therapies and the importance of early detection and management of CKD. 37 …”
Section: Screening and Early Diagnosis Of Ckd In Meamentioning
confidence: 99%
“…[73][74][75][76] Enhancing the knowledge of frontline primary care physicians and patients for cardiorenal benefits of SGLT-2i and risk control, addition of SGLT-2i by policymakers as crucial performance indicator along with glycemic control, adoption of multidisciplinary team-based care strategies, and providing access to financial assistance programs can improve the uptake of SGLT-2i for management of CKD. 37,76,77…”
Section: Dovepressmentioning
confidence: 99%